The Effect of Using Quantum Teaching and Cooperative Integrated Reading and Composition Methods on the Ability to Write Descriptions of Elementary School Students - Muh Maskur; Tarman Andi Arief; Andi Syukri Syamsuri (Pedagogik Journal of Islamic Elementary School, 2023)
This study aims to determine the effect of the quantum teaching and cooperative integrated reading and composition methods on students' ability to write descriptions. This research is a quasi-experimental research. The location of this research was SDN 261 Bilangporoa, Bulukumba district. Determining the subject of this study using simple random sampling technique with a total of 60 students. Data collection techniques used written tests. Data analysis in this study used the t test and ANOVA. The results of the study stated that from the third class, two experimental classes and one control class experienced an increase, but the experimental class improved better than the control class, where the posttest value of the quantum teaching experiment was 72.25, the integrated cooperative reading and composition experiment was 72.50 and the with conventional methods 66.40. For the inertial analysis results of the quantum teaching class using the independent t test a significance value of 0.017 was obtained and cooperative reading class and integrated composition were 0.013 and for the posttest ANOVA test results a significance value of 0.017 was obtained.